2020
DOI: 10.1002/jib.597
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and comparison of the microflora of traditional and pure culturexiaoquduring thebaijiuliquor brewing process

Abstract: Light flavour baijiu, one the three major types of liquor in China, is popular with consumers, particularly in northern China. To understand how microbial communities and physical and biochemical properties change during the brewing process, two groups of xiaoqu -traditional and pure culture -were used for fermentation. High-throughput sequencing (HTS) combined with isolation and identification of microorganisms were used to investigate the microbial community dynamics during the brewing process. The tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
2
17
4
Order By: Relevance
“…At the late stage of fermentation, the anaerobic environment is dominant, the nutrient content decreases, and the acidity and alcoholic content increases, which inhibit the growth of some microorganisms and lead to a decrease in species diversity. The changing pattern of microbial diversity is consistent with that in the brewing of strong- ( Tan et al, 2019 ; Guan et al, 2020 ), mixed- ( Liu and Miao, 2020 ), and light-flavor baijiu ( Dong et al, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…At the late stage of fermentation, the anaerobic environment is dominant, the nutrient content decreases, and the acidity and alcoholic content increases, which inhibit the growth of some microorganisms and lead to a decrease in species diversity. The changing pattern of microbial diversity is consistent with that in the brewing of strong- ( Tan et al, 2019 ; Guan et al, 2020 ), mixed- ( Liu and Miao, 2020 ), and light-flavor baijiu ( Dong et al, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
“…are more likely to undergo homolactic fermentation, which is the main reason for the rapid increase in ethyl lactate content and only a small increase in acetic acid and ethyl acetate content at the late stage of fermentation. The main bacterial genera in the Xiaoqu light-flavor baijiu were Lactobacillus , Acetobacter , Weissella , Lactococcus , and Bacillus ( Dong et al, 2020 ; Hu et al, 2021a , b ). In strong-flavor baijiu, the main bacteria genera were Kosakonia , Lactobacillus , Weissella , Pediococcus , Pantoea , and Bacillus , which accounted for more than 86% of the bacterial abundance ( Guan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Basidiomycota was predominantly dominant in AS (2.28%) and HS (1.77%; Figure 1B ). Firmicutes, Proteobacteria, and Actinobacteria were previously identified as the dominant bacteria in Xiaoqu (Wu H. et al, 2017 ), Xiaoqu jiu (Dong et al, 2020 ), and strong-flavored Baijiu fermentation ecosystems (Zou et al, 2018 ). Meanwhile, Ascomycota, Mucoromycota, and Basidiomycota occupy a major position in the brewing process of black glutinous rice wine (Zhao et al, 2020 ), Indian dry starters (Anupma and Tamang, 2020 ), and strong-flavor Baijiu Daqu (Guan et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the abundances of Rhizopus and Phycomyces were 13.64 and 11.26% and 13.24 and 10.90% in AS and HS, respectively. Rhizopus , a strong amylase producer that degrades starch during Xiaoqu jiu production (Tang et al, 2019 ; Dong et al, 2020 ), was previously identified as the main fungi in Wuyi Qu (Liu et al, 2018 ). Conclusively, the microbiota detected in these Xiaoqu samples demonstrated significant differences in their structure and diversity, which might be due to differences in geographical environment, raw materials, and preparation technology (Du et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%